On De-imagination as a Regime: Technique and Algorithmisation - Borisonik, Hernan Gabriel (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
This article develops the notion of “de-imagination” as a central part of the contemporary political-technological regime in which the imaginative faculty is captured by algorithmic governmentality (Rouvroy and Berns). The concept is developed from the idea of active production which, through exomatisation (Stiegler) and predictive standardisation, closes off alternative futures and the medial power of radical imagination. Drawing on philosophical archaeology and in dialogue with Hannah Arendt, Giorgio Agamben, Cornelius Castoriadis (social imaginary) and Jacques Rancière (distribution of the sensible), the text seeks to situate imagination as a central field of political dispute. Finally, in opposition to this regime, it proposes an eroticism of the future as a practice of profanation which, through inoperability and aesthetic reappropriation, can liberate the instituting power of the common.